Preservative effect of various indigenous plants on fermented milk from Maasai community of Kajiado County - Onyango, C. A.; Gakuya, L. W.; Mathooko, Francis M.; Maina, J. M.; Nyaberi, M. O.; Makobe, M.; Mwaura, F (My University, 2014)
Objective: This study was conducted to verify the claim that incorporation of indigenous plants in milk extends the shelf life of fresh milk for four days, and that of fermented milk for up to one a month without spoilage. Methodology and results: In this study, three indigenous plants namely Lippia javanica, Olkingiri and Olea europaea used by the Maasai community in Kajiado district to process and preserve milk were collected from the field. An aqueous extract concentration of 40mg/ml was prepared from each of the plants and introduced into each milk sample with a control that did not have the extract. Between the third day and the 14th day the fermented milk was analyzed every second day for aerobic plate count using method 966.23 (AOAC. 1995), titratable acidity using method 947.05 (AOAC, 1995) and pH changes. Aerobic plate counts increased constantly in all the samples, the highest was the control with counts of 10.00 – 11.40 log cfu/ml and the lowest was milk with Olea europaea with counts of 5.05 – 8.38 log cfu/ml. The control exhibited the highest titratable acidity of 1.08 - 1.87% while that treated with Olea europaea had 0.41 – 0.98%. Fermented milk without treatment had the lowest pH of between 4.18 – 3.73 while the highest pH was exhibited by fermented milk with Olea europaea of between 5.33-4.29. Conclusion and application: Fermented milk treated with plant extracts had better quality properties than fermented milk without any treatment; therefore, the Maasai community in Kajiado County is justified to use these herbs to process and preserve milk. This practice should be made available for commercial use. Keywords: Indigenous plants, fermentation